A measurement method for bending deflection of hexagonal shaft based on contour reconstruction. (December 2021) - Pei, Yong-Chen; Yuan, Yi; Li, Hao; Wang, Cong-Hui
Graphical abstract: Highlights: Non-contact measurement method is proposed for hexagonal shaft bending deflection. The valid data is extracted within the allowable incident angle of laser sensor. The measurement accuracy can reach the same level as ZEISS Calypso scanner. High precision, high efficiency, non-rotation speed limited are method advantages. Abstract: The hexagonal shaft is often used as the important transmission component. Its bending deflection is a main factor affecting the working capability and fatigue life. In this paper, a contactless continuous measurement method based on contour reconstruction is proposed, which only uses a laser displacement sensor moving at a constant speed to collect the profile information. According to the allowable incident angle, the valid data with high precision is extracted. An algorithm seeking for section center is deduced according to the hexagon edge equations fitted by the least square method, then, the three-dimensions blending axis is obtained. The method precision is analyzed by theoretical error analysis. Finally, the feasibility and high accuracy of the novel method are demonstrated by comparing with ZEISS Calypso scanner results and the repeatability and reproducibility (R&R) analysis.